Human Speech and God's Word: On a Latent Divine Attribute - Tóth, Beáta (2020)
The idea that God speaks to humans and responds to their call is often taken for granted in the Judeo-Christian tradition. This paper reflects on the significance of the fact that God is Deus loquens: one who speaks in revelation and who is also inner Trinitarian eternal utterance. To outline an anthropology and a theology of speech, two Hungarian interlocutors are summoned: twentieth century poet János Pilinszky (1921-1981) and exegete and literary critic István Jelenits (b. 1932), whose accounts are instructive concerning the nature of human and divine communication. As a next step, the post-synodal apostolic exhortation Verbum Domini (2010) by Pope Benedict XVI is examined, which can be seen as providing the outlines of a systematic “theology of the word.” Such theology is aware that the word of God is an analogical concept rooted in the Trinitarian reality of divine communication.
Keywords: Verbum Domini; Benedict XVI; István Jelenits; János Pilinszky; God's Word